Synthesis of Nitroxide End‐Labeled Polymers by Capturing Polystyrene Radicals with Spin Traps. Issue 20 (13th September 2018) - Heiler, Katherine E.; Pan, Ching W.; Heiler, Alexander J.; Wu, Jessica P.; Tillman, Eric S.
Abstract: Atom transfer radical polymerization is used to synthesize brominated polystyrene, and the alkyl halide chain end is transformed into a nitroxide radical by the addition of excess nitrosobenzene to a redox active reaction mixture. The nitroxide group at the chain is verified using gel permeation chromatography, UV–vis, and electron paramagnetic resonance spectroscopy, showing the addition of the nitroso group does not result in a doubling of molecular weight, with the resulting polymer possessing new absorptions in the 300–400 nm range and an unpaired electron. The nature of the radical trap plays a role in halting the reaction at the end‐capped nitroxide polymer, rather than undergoing dimerization via atom transfer radical coupling‐type pathways. The polymeric nitroxide radical can be used to trap a second polymer radical in a subsequent reaction, simply by reacting with a second bromine‐capped polymer and adjusting the redox activity of the solution. Abstract : Nitroxide‐capped polymers are prepared by activating brominated polymer chains in the presence of nitroso radical traps, with unwanted dimerization almost entirely suppressed. The structure of the radical trap, and its ratio to polymer chains, are the most important experimental considerations in achieving high yields of the nitroxidelabeled polymer. The nitroxide end group is verified with electron paramagnetic resonance spectroscopy.